Tolerance, safety, and effect on the faecal microbiota of an enteral formula supplemented with pre- and probiotics in critically ill children - Nipat Simakachorn (2018)
Objectives: The aim of this study was to demonstrate the tolerance and safety of an enteral formula containing prebiotics/probiotics, and its effect on the faecal microbiota in critically ill children. Subjects and Methods: Ninety-four patients between 1 and 3 years old under mechanical ventilation requiring enteral feeding were randomised to receive either a test formula containing a synbiotic blend (composed of 2 probiotic strains [Lactobacillus paracasei NCC 2461 and Bifidobacterium longum NCC 3001], fructooligosaccharides [FOS] , inulin, and Acacia gum), or a control formula. Patients remained in the intensive care unit for 7 days and were examined at day 14. Tolerance was assessed by overall caloric intake and time to reach caloric goal. Safety was assessed by abdominal distention, vomiting, and stool frequency. Microbiota was analysed by culture- and molecular-based methods. Results: Overall caloric intake and time to reach caloric goal were similar between groups (noninferiority was shown). Abdominal distention, vomiting, and stool frequency were not affected by the supplementation with pre- and probiotics. Faecal bifidobacteria were higher in the test group at the end of the study. A similar trend was observed for total lactobacilli. L paracasei NCC 2461 and B longum NCC 3001 were detected in 80.4% and 17% of the test group patients, respectively. Enterobacteria levels remained unchanged during hospitalisation in the control group but diminished in the test group. Conclusions: The enteral formula supplemented with synbiotics was well tolerated by children in intensive care units; it was safe and produced an increase in faecal bacterial groups of previously reported beneficial effects. Copyright © 2011 by European Society for Pediatric Gastroenterology, Hepatology, and Nutrition and North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition.